Biosynthesized silver nanoparticles to control fungal infections in indoor environments - Deyá, Marta Cecilia (2017)
Fungi grow especially in dark and moist areas, deteriorating the indoor environment and causing infections that particularly affect immunosuppressed individuals. Antimicrobial coatings have as principal objective to prevent biofilm formation and infections by incorporation of bioactive additives. In this sense, metallic nanoparticles, such as silver, have proven to be active against different microorganisms specially bacteria. Biosynthesized method is a promising environmentally friendly option to obtain nanoparticles. The aim of this research was assess the employment of plants extracts of Aloysia triphylla (cedrón), Laurelia sempervirens (laurel) and Ruta chalepensis (ruda) to obtain silver nanoparticles to be used as an antimicrobial additive to a waterborne coating formulation. The products obtained were assessed against fungal isolates from biodeteriorated indoor coatings. The fungi were identified by conventional and molecular techniques as Chaetomium globosum and Alternaria alternate. The results revealed that the coating with silver nanoparticles obtained with L. sempervirens extract at 60 °C with a size of 9.8 nm was the most efficient against fungal biofilm development.